Measurement Invariance and Construct Validity of the Turkish Version of the Learner Autonomy Scale in a Sample of High and Secondary School Students - Kazu, Hilal; Deniz, Emrullah (Asya Publishing and Consultancy, 2024)
The aim of this research is to adapt the 24-item "Learner Autonomy Scale" developed by Sereti and Giossos (2018) in higher education samples into Turkish by examining the psychometric properties of high school and secondary school samples, and to determine whether these groups are equivalent in terms of measurement invariance. The scale was applied in high school (n = 475) and secondary school (n = 395) samples consisting of 870 students. Different from the original four-factor scale form, EFA applied to both groups revealed a two-factor (factor load range: .308-.775) and 21-item. Correlation values (r = .209-.392, p?.001) indicate that the factors are not strongly related. The factors produced adequate internal consistency coefficients (? = .706-.866; ? = .708-.871) and were validated by meeting the fit indices accepted in the literature for CFA. Measurement invariance tests revealed strong invariance for the structural and metric tests and partial invariance for the scalar test in high school and secondary school samples. More research is needed to determine why the intersections of items 19, 20, and 21 are not invariant. The main contribution to "learner autonomy" in this study is the adaptation and justification of a valid and reliable measurement tool for determining autonomy in the adolescent age group. The use of the adapted scale in different educational environments and in the examination of "autonomy" by adapting it specific to the field (science, mathematics, etc.) will provide important implications for further theoretical studies. © 2024, Asya Publishing and Consultancy. All rights reserved.
Keywords: Autonomy; Learner autonomy; Measurement invariance; Scale adaptation